Comparison of retinal image quality with spherical and customized aspheric intraocular lenses - Guo, Huanqing (Optical Society of America, 2012)
We hypothesize that an intraocular lens (IOL) with higher-order aspheric surfaces customized for an individual eye provides improved retinal image quality, despite the misalignments that accompany cataract surgery. To test this hypothesis, ray-tracing eye models were used to investigate 10 designs of mono-focal single lens IOLs with rotationally symmetric spherical, aspheric, and customized surfaces. Retinal image quality of pseudo-phakic eyes using these IOLs together with individual variations in ocular and IOL parameters, are evaluated using a Monte Carlo analysis. We conclude that customized lenses should give improved retinal image quality despite the random errors resulting from IOL insertion.